Arthroscopic Subpectoral Tenodesis of the Long Head of the Biceps Brachii - Alexander J. Hoffer, M.D., M.Sc., F.R.C.S.C.; John M. Tokish, M.D. (Arthroscopy Techniques)
The long head of the biceps brachii is a common pain generator in the shoulder that is often managed surgically with tenotomy or tenodesis. The clinical outcomes after tenotomy and tenodesis are comparable. However, tenodesis is preferred in the active population owing to complications associated with tenotomy, including cosmetic deformity, early fatigue, and cramping. Controversy surrounds both the approach and location of tenodesis. Both open and arthroscopic techniques have been described. An arthroscopic approach is used for tenodesis within the intertubercular groove between the humeral head articular margin and superior border of the pectoralis major but has the drawback of pathologic tendon retained in the groove. An open approach is generally reserved for subpectoral tenodesis, which has the advantage of no retained pathologic tendon but has the drawbacks of an open approach. We describe an all-arthroscopic technique for subpectoral tenodesis of the long head of the biceps brachii at the lower border of the pectoralis major.